2018
DOI: 10.1097/iae.0000000000001759
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Inner Retinal Layer Thicknesses in Age-Related Macular Degeneration Using Corrected Optical Coherence Tomography Segmentation

Abstract: In patients with dry AMD, automatic optical coherence tomography segmentation algorithms may be erroneous. As the severity of dry AMD increases, the inner plexiform layer layer becomes thinned, suggesting that transsynaptic degeneration may be occurring, as the photoreceptor layer is affected by AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 19 publications
(25 reference statements)
5
52
3
Order By: Relevance
“…Recently, automated segmentation software programmes that enable analysis layers of the retina qualitatively and quantitatively have been introduced [15,16]. Using these softwares, recent studies of AMD eyes have demonstrated that there were a change not only in the outer retinal layers as previously established but also in the inner retina such as the ganglion cell complex (GCC) thickness, which includes GCL and inner plexiform layer (IPL) [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, automated segmentation software programmes that enable analysis layers of the retina qualitatively and quantitatively have been introduced [15,16]. Using these softwares, recent studies of AMD eyes have demonstrated that there were a change not only in the outer retinal layers as previously established but also in the inner retina such as the ganglion cell complex (GCC) thickness, which includes GCL and inner plexiform layer (IPL) [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Acquisition of raster scans at high resolution is well tolerated by patients and does generally require fewer skills by the operator as compared to stereoscopic CFP. For quantitative analysis of drusen volume and its changes over time, serial data of various numbers of B-scans are obtained and the borders of the BM/RPE complex are segmented in each B-scan using semi-automated algorithms [19]. Until more reliable and validated algorithms become available, the segmentation in each B-scan must be reviewed and manually corrected as indicated because current semiautomated algorithms are prone to segmentation errors, particularly in eyes with intermediate AMD [19].…”
mentioning
confidence: 99%
“…For quantitative analysis of drusen volume and its changes over time, serial data of various numbers of B-scans are obtained and the borders of the BM/RPE complex are segmented in each B-scan using semi-automated algorithms [19]. Until more reliable and validated algorithms become available, the segmentation in each B-scan must be reviewed and manually corrected as indicated because current semiautomated algorithms are prone to segmentation errors, particularly in eyes with intermediate AMD [19]. Considering future trials on intermediate AMD, larger data sets demand an increasing amount of work and time for analysis of dynamic changes in drusen volume over time.…”
mentioning
confidence: 99%
“…52,53 The GCC was analyzed using automatic segmentation without checking the accuracy of delineation of segmented retinal layers, explaining the high error rate. Recently, Muftuoglu et al 54 also reported GCC changes in patients with severe dry AMD even using the manual correction of segmentation.…”
Section: Discussionmentioning
confidence: 99%